Haemostatic therapies for acute spontaneous intracerebral haemorrhage - Al-Shahi Salman, Rustam; Law, Zhe Kang; Bath, Philip M.; Steiner, Thorsten; Sprigg, Nikola (Wiley, 2018)
Background: Outcome after spontaneous (non-traumatic) intracerebral haemorrhage (ICH) is influenced by haematoma volume; up to one-third of ICHs enlarge within 24 hours of onset. Early haemostatic therapy might improve outcome by limiting haematoma growth. This is an update of a Cochrane Review first published in 2006, and last updated in 2009. Objectives: To examine 1) the effectiveness and safety of individual classes of haemostatic therapies, compared against placebo or open control, in adults with acute spontaneous intracerebral haemorrhage, and 2) the effects of each class of haemostatic therapy according to the type of antithrombotic drug taken immediately before ICH onset (i.e. anticoagulant, antiplatelet, or none). Search methods: We searched the Cochrane Stroke Trials Register, CENTRAL; 2017, Issue 11, MEDLINE Ovid, and Embase Ovid on 27 November 2017. In an effort to identify further published, ongoing, and unpublished randomised controlled trials (RCT), we scanned bibliographies of relevant articles and searched international registers of RCTs in November 2017. Selection criteria: We sought randomised controlled trials (RCTs) of any haemostatic intervention (i.e. pro-coagulant treatments such as coagulation factors, antifibrinolytic drugs, or platelet transfusion) for acute spontaneous ICH, compared with placebo, open control, or an active comparator, reporting relevant clinical outcome measures. Data collection and analysis: Two authors independently extracted data, assessed risk of bias, and contacted corresponding authors of eligible RCTs for specific data if they were not provided in the published report of an RCT. Main results: We included 12 RCTs involving 1732 participants. There were seven RCTs of blood clotting factors versus placebo or open control involving 1480 participants, three RCTs of antifibrinolytic drugs versus placebo or open control involving 57 participants, one RCT of platelet transfusion versus open control involving 190 participants, and one RCT of blood clotting factors versus fresh frozen plasma involving five participants. We were unable to include two eligible RCTs because they presented aggregate data for adults with ICH and other types of intracranial haemorrhage. We identified 10 ongoing RCTs. Across all seven criteria in the 12 included RCTs, the risk of bias was unclear in 37 (44%), high in 16 (19%), and low in 31 (37%). Only one RCT was at low risk of bias in all criteria. In one RCT of platelet transfusion versus open control for acute spontaneous ICH associated with antiplatelet drug use, there was a significant increase in death or dependence (modified Rankin Scale score 4 to 6) at day 90 (70/97 versus 52/93; risk ratio (RR) 1.29, 95% confidence interval (CI) 1.04 to 1.61, one trial, 190 participants, moderate-quality evidence). All findings were non-significant for blood clotting factors versus placebo or open control for acute spontaneous ICH with or without surgery (moderate-quality evidence), for antifibrinolytic drugs versus placebo (moderate-quality evidence) or open control for acute spontaneous ICH (moderate-quality evidence), and for clotting factors versus fresh frozen plasma for acute spontaneous ICH associated with anticoagulant drug use (no evidence). Authors' conclusions: Based on moderate-quality evidence from one trial, platelet transfusion seems hazardous in comparison to standard care for adults with antiplatelet-associated ICH. We were unable to draw firm conclusions about the efficacy and safety of blood clotting factors for acute spontaneous ICH with or without surgery, antifibrinolytic drugs for acute spontaneous ICH, and clotting factors versus fresh frozen plasma for acute spontaneous ICH associated with anticoagulant drug use.